1977
DOI: 10.1021/j100523a008
|View full text |Cite
|
Sign up to set email alerts
|

Two-constant model to describe amine and alcohol association from vapor pressure measurements

Abstract: Publication costs assisted by Fonds der Chemie, Frankfurt these bonds as the bonds of cyclic dimers and linear higher polymers, as suggested by previous authors. However, due to the complications of the alcohol association as well as to the inherent simplifications of the model the calculated energies may not be related to the bonds in a simple manner. From K2 and K3 the activity coefficients and the excess free energy can be recalculated. The comparison of the obtained values with the conventionally calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 2 publications
1
28
0
Order By: Relevance
“…An alkan-1-ol and amine are associated by formation O-H Á Á Á O and N-H Á Á Á N hydrogen bonds. From vapour pressure and spectroscopic measurements, it has been shown that the dimerisation energy and the energy of the formation of higher oligomers are nearly the same, (8.5 to 13.5) kJ AE mol À1 for the amines and (20 to 25.1) kJ AE mol À1 for the alcohols [19]. Usually, it is assumed that in amines one kind of hydrogen bond, probably a linear bond, occurs and that in alcohols two kinds of hydrogen bonds are present, leading to cyclic dimmers and linear higher oligomers, depending on the length of the alcohol chain.…”
Section: Sle and Llementioning
confidence: 99%
See 1 more Smart Citation
“…An alkan-1-ol and amine are associated by formation O-H Á Á Á O and N-H Á Á Á N hydrogen bonds. From vapour pressure and spectroscopic measurements, it has been shown that the dimerisation energy and the energy of the formation of higher oligomers are nearly the same, (8.5 to 13.5) kJ AE mol À1 for the amines and (20 to 25.1) kJ AE mol À1 for the alcohols [19]. Usually, it is assumed that in amines one kind of hydrogen bond, probably a linear bond, occurs and that in alcohols two kinds of hydrogen bonds are present, leading to cyclic dimmers and linear higher oligomers, depending on the length of the alcohol chain.…”
Section: Sle and Llementioning
confidence: 99%
“…Usually, it is assumed that in amines one kind of hydrogen bond, probably a linear bond, occurs and that in alcohols two kinds of hydrogen bonds are present, leading to cyclic dimmers and linear higher oligomers, depending on the length of the alcohol chain. Two-constant models for the association of alcohols within a wide range of concentrations are not used for the hexan-1-ol and longer chain alcohols [19].…”
Section: Sle and Llementioning
confidence: 99%
“…Primary and secondary amines are weakly self-associated [1][2][3][4][5][6][7][8]. Note that their Trouton's constants (table 1) are close to the value of non-associated species (92.05 J Á mol À1 Á K À1 [9]).…”
Section: Introductionmentioning
confidence: 84%
“…It is well known that in the pure state the amines are weakly associated by the formation of N HÁÁÁN hydrogen bonds. From vapour pressure and spectroscopic measurements, it has been shown that the dimerisation energy and the energy for the formation of higher oligomers are nearly the same, ranging from 8.5 to 13.5 kJ Á mol À1 [10][11][12]. Although phase equilibria of amines and their mixtures have been extensively studied, the thermodynamic phase properties have received less attention.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the relevant question is the association phenomenon is strong enough to affect the heat capacity behaviours of 1-amines? A literature review reveals that very few data [11,16] are available for amines. In this context, experimental heat capacities of 1-pentylamine and 1-hexylamine were determined in extended ranges of pressure and temperature.…”
Section: Introductionmentioning
confidence: 99%